Detection of peptide‐binding sites on protein surfaces: The first step toward the modeling and targeting of peptide‐mediated interactions. Issue 12 (17th October 2013) - Lavi, Assaf; Ngan, Chi Ho; Movshovitz‐Attias, Dana; Bohnuud, Tanggis; Yueh, Christine; Beglov, Dmitri; Schueler‐Furman, Ora; Kozakov, Dima; Bonvin, Alexandre M. J. J.; Janin, Joël; Wodak, Shoshana J.
Abstract Peptide‐mediated interactions, in which a short linear motif binds to a globular domain, play major roles in cellular regulation. An accurate structural model of this type of interaction is an excellent starting point for the characterization of the binding specificity of a given peptide‐binding domain. A number of different protocols have recently been proposed for the accurate modeling of peptide‐protein complex structures, given the structure of the protein receptor and the binding site on its surface. When no information about the peptide binding site(s) is a priori available, there is a need for new approaches to locate peptide‐binding sites on the protein surface. While several approaches have been proposed for the general identification of ligand binding sites, peptides show very specific binding characteristics, and therefore, there is a need for robust and accurate approaches that are optimized for the prediction of peptide‐binding sites. Here, we present PeptiMap, a protocol for the accurate mapping of peptide binding sites on protein structures. Our method is based on experimental evidence that peptide‐binding sites also bind small organic molecules of various shapes and polarity. Using an adaptation of ab initio ligand binding site prediction based on fragment mapping (FTmap), we optimize a protocol that specifically takes into account peptide binding site characteristics. In a high‐quality curated set of peptide‐protein complex structures PeptiMap identifies for most the accurate site of peptide binding among the top ranked predictions. We anticipate that this protocol will significantly increase the number of accurate structural models of peptide‐mediated interactions. Proteins 2013; 81:2096–2105. © 2013 Wiley Periodicals, Inc.